ULTRASONOGRAPHIC ASSESSMENT OF HEPATIC STEATOSIS AND ITS CORRELATION WITH BMI AND SERUM PARAMETERS OF LIVER FUNCTION IN NON- ALCOHOLIC FATTY LIVER DISEASE (The Research of Medical Science Review, 2025)
BACKGROUND: The prevalence of non-alcoholic fatty liver disease (NAFLD) is high in the Western population and is on the rise globally. Similar to alcohol-induced liver damage, pathological alterations in fatty liver can result in end-stage liver disease. Obese or overweight individuals have a higher frequency of non-alcoholic fatty liver disease (NAFLD) than the general population, and it appears that those with a high body mass index (BMI) or abnormalities in certain laboratory tests are more likely to have severe fatty liver and high-grade NAFLD on ultrasonography (U.S.). OBJECTIVE: To evaluate the correlation of BMI and laboratory tests (Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST)), with ultrasonographic grades assessment of hepatic steatosis. MATERIALS AND METHODS: It was a cross-sectional study. Our study was carried out in the Department of Radiology, Pakistan Kidney and Liver Institute, Lahore. A sample size(n) of 35 patients was estimated by the use of the following formulae; Total sample size= N= [(Zα+Zβ)/C]2 + 3= 35 Where, C= 0.5* ln[(1-r)] = 0.5763, Zα= 1.9600, Zβ= 1.2816, (r= 0.562) (19). Non-probability consecutive sampling technique was used. Inclusion criteria as adult patients of both genders over the age of 18, fatty liver on U.S diagnosed if the liver echogenicity is more than that of the renal cortex and spleen and there was attenuation of ultrasound wave, loss of diaphragm contour, and poor outlining of the intrahepatic architecture. After the approval from ethical research committee,  informed consent was taken from the patients fulfilling the inclusion criteria. Data analysis was done using the statistical package for social sciences (SPSS) version 20. The p-value ≤ 0.05 was considered as significant. RESULTS: We discovered that 49.19% of the study group had hepatic steatosis, and 65% of the patients were overweight or obese when they first arrived. Hepatic steatosis was closely associated with a drop in HDL and an increase in AST, and GGT; this incidence was higher in men. The best predictors, according to an ordinal logistic regression model, were BMI and AST. CONCLUSION: According to our findings, the most useful indicators of fatty liver disease severity and ultrasonography grade (USG) in patients with NAFLD are BMI and BMI, however, can be useful as a predictor. However, because AST varies depending on a number of factors, it has not proven a trustworthy result.